Telemedicine for diabetes management during COVID-19: what we have learnt, what and how to implement - Rosta, Laszlo; Menyhart, Adrienn; Mahmeed, Wael Al; Al-Rasadi, Khalid; Al-Alawi, Kamila; Banach, Maciej; Banerjee, Yajnavalka; Ceriello, Antonio; Cesur, Mustafa; Cosentino, Francesco; Firenze, Alberto; Galia, Massimo; et al. (Frontiers in Endocrinology, 2023)
The past two decades have witnessed telemedicine becoming a crucial part of health care as a method to facilitate doctor-patient interaction. Due to technological developments and the incremental acquisition of experience in its use, telemedicine’s advantages and cost-effectiveness has led to it being recognised as specifically relevant to diabetology. However, the pandemic created new challenges for healthcare systems and the rate of development of digital services started to grow exponentially. It was soon discovered that COVID-19-infected patients with diabetes had an increased risk of both mortality and debilitating sequelae. In addition, it was observed that this higher risk could be attenuated primarily by maintaining optimal control of the patient’s glucose metabolism. As opportunities for actual physical doctor-patient visits became restricted, telemedicine provided the most convenient opportunity to communicate with patients and maintain delivery of care. The wide range of experiences of health care provision during the pandemic has led to the development of several excellent strategies regarding the applicability of telemedicine across the whole spectrum of diabetes care. The continuation of these strategies is likely to benefit clinical practice even after the pandemic crisis is over.